(untitled) (Revista CICSA online, serie nouă/ CICSA Journal online, New Series, 2025)
This work represents the effort of a collective of researchers from different backgrounds but with a single purpose: to analyze the anthropic behaviors by means of stable isotopes in addition to the traditional methods of archeological frameworks. Application of multi-isotopic analyses can shed a new light on how human behavior is interpreted in different circumstances but also the limitations of these type of studies. The presented case studies from experts from different backgrounds are structured in a specific manner to be understood by researchers who are not specialized in stable isotopes, and targets researchers and students alike by providing different approaches for archaeologists how to interpret and analyze the data resulted from multi-isotopic analysis but also what to expect from these types of investigations.